ENERGY POTENTIAL OF FLUE GAS ALUMINUM SMELTING FURNACE SOLAR FUEL WITH THE ADDITION OF TEAK WOOD PELLETS - Sutoyo; Muhammad Shomad; Sunaryo (Clean Energy and Smart Technology, 2023)
The choice of fuel (fuel oil) whose price is higher needs a solution, especially for conventional foundry entrepreneurs. We need alternative energy that is cheap and easy to get. Wood pellets are an attempt to replace fuel with cheap fuel. As with previous studies, the main objective of this study was to measure the energy potential of the smelting furnace flue gas. The analysis results show that 365,413.3 kJ of heat energy is wasted from the total point required for smelting. The flames sometimes coming out of the furnace flue gas channel indicate that some heat energy is smashed into the free air. The exhaust gas temperature is measured at 500-550⁰C, and you can see flashes of fire coming out frequently. This indicates that there is energy potential for the working process of the pyrolysis reactor; apart from that, the moments of fire that often appear indicate an excess of the combustion process in the furnace. This study's results may differ from other smelting furnace constructions and conditions.